Optimizing material selection and the thickness of radon reduction layer in uranium tailings pond - Deng, Nianbiao; Ding, Dexin (Journal of radioanalytical and nuclear chemistry, 2024)
In this paper, a multi-objective decision model is formulated utilizing both single-layer and three-layer radon reduction layer materials by considering radon emanation rate and cost as decision objectives. Through a multi-objective non-dominated ranking method, the optimal solution is identified from a range of feasible alternatives. In the case of the example uranium tailings pond, the optimized three-layer radon reduction layer materials reduce the comprehensive cost by 47.8% compared with the single-layer radon reduction layer materials while meeting the radon emanation rate limit. Furthermore, the utilization of non-dominated multi-objective optimization techniques demonstrates higher efficiency in optimizing each radon reduction layer schemes.